The relative profitability of forestry and agriculture on the Manawatu-Rangitikei sand country : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the Massey University of Manawatu - Chisholm, Anthony Hewlings (Massey University, 1963)
This Discussion Paper is aimed at making Anthony Chisholm's Master's thesis more widely available than would otherwise be possible. The thesis is reproduced as originally presented, except for the transfer of a technical description of the sand country soils from the main text to Appendix XII, The explicit findings of Chisholm's study (summarized in Chapter VII) are that approximately 39,000 acres of the poorest sand country soil types should be developed for forestry rather than sheep farming. At present only 15,000 acres of this land has been allocated to forestry. The author has calculated that the development of the remaining 24,000 acres into forests would yield revenue with a present value £400,000 greater than that to be attained by continuing its development for farming. The land use recommendations made by Chisholm are tabulated in this preface. More important, in my view, than the explicit recommendations, is the example which this study provides of the objective evaluation of the profitability of alternative land uses. The expected yields, development costs, and returns from both forestry and farming have been carefully laid out, and the present value of land used for farming and forestry has then been calculated. [FROM PREFACE]
Keywords: New Zealand -- Manawatu; Forests and forestry; Agriculture